PENGEMBANGAN MODEL PERMAINAN SMOOTH BALL DALAM PEMBELAJARAN ROUNDERS (Department of Physical Education, Sport, Health and Recreation, 2014)
This study aims to produce a model of the game of smooth ball on class V students, secondary the students more active, innovative and entertaining.The research was conducted at SDN 01 Soditan Sub-district Lasem District Rembang, the sample in this study is the students of five grade primary class. This research is a development that consists of a small group (18 students), and field trials (36 students), research development consists of planning, observation and action observation, and reflection. Data collection techniques in this study using the expert evaluation sheet used to collect data from experts and questionnaires were used to collect data from expert and student evaluation. Test result data obtained by the expert evaluation data, expert penjas 93,33% (excellent), learning experts 94,7% (excellent), a small group of test results obtained questionnaires psychomotor aspects of 89,98%, 91,1% cognitive, and affective 98,33%, of the overall results of the student questionnaire small test group obtained a percentage of 93,14% (excellent), and a field test of psychomotor aspects of the questionnaire obtained 91,67%, 92,77% cognitive, and affective 99,16%, the overall results of the field test questionnaire obtained a percentage of 94,53% (excellent). From the available data it can be concluded that the model of learning smooth ball cart moves can be used for students of SDN 01 Soditan Sub-district Lasem District Rembang.